MENINGKATKAN PRESTASI KERJA DI LINGKUNGAN PERBANKAN - Abdul Azis (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2019)
The purpose of the organization is profit, and employee performance is the answer. Therefore, companies work together to develop HR, through training, education, rotation, promotion, compensation, career paths, facilities, and others. On this basis, this study was conducted to analyze the determinants of work performance. To test this research, several methods were carried out including the quantitative approach method, using a questionnaire as a data collection instrument with a Likert scale as a parameter, using multiple linear regression analysis method which includes descriptive analysis, validity test, reliability test, classic assumption test, partial test, simultaneous test, and coefficient of determination test. The object of this research is the Mayora bank in Jakarta with 99 respondents. The results showed there were positive and significant effects of training, motivation and compensation on employee work performance. That is, to be able to improve performance to the maximum, the company must provide ongoing training, provide work motivation (moral or material), and provide appropriate compensation